APLIKASI SISTEM INFORMASI PEMANDU WISATA DAERAH BANDA NEIRA BERBASIS ANDROID - Ahmad Thariq; Dwi F Pattiha (Universitas Nusa Cendana, 2023)
Tourism is a means to introduce a region's natural beauty and cultural uniqueness. Maluku Province, especially in Eastern Indonesia, has a sub-district called Banda Neira. Tourism potential includes historical tourism, nature tourism, and cultural tourism. However, disseminating information about tourist attractions in Banda Neira is still lacking because some information on the internet is not updated, there are no plans or directions to get to a tourist location and some historical information boards of tourist locations are also damaged or even non-existent. An android-based application was made as an answer using android studio tools, and the model used is the prototype. The final result of this application is that it can provide information about various tourist attractions equipped with pictures and maps to make it easier for visitors to choose places to visit while travelling.